P-B28 Dichotomous effects of immune based (Interferon-alpha) and Non-immune based (direct acting antiviral) therapies on lipid biosynthesis. (January 2016) - Tang, Lydia; Emmanuel, Benjamin; Kottilil, Shyam
Abstract : Chronic hepatitis C (HCV) infection is associated with dyslipidemia. Neither the underlying mechanisms nor the impact of treatment are understood. HCV is now treated with interferon (IFN)-free, direct acting antiviral (DAA)-only therapy. Here, we delineate the effects of IFN-based and IFN-free DAA therapy on lipid profiles in chronic HCV patients. Veterans cured with IFN-containing therapy between 2011 and 2013 at the Baltimore VA Medical Center were identified. Baseline, end of treatment (EOT), and 1-year post-EOT total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) values were analyzed. Baseline, 8 weeks post EOT and 1 year post EOT lipids were also evaluated among patients cured with DAA-only therapy (6 weeks of ledipasvir/sofosbuvir+GS9451 or GS9669). Changes in mean were analyzed with the paired t-test. Lipids for 29 veterans were analyzed. Mean LDL decreased on treatment by 10.7% (baseline 110.4 to EOT 98.6 mg/dL, P = 0.089), followed by a significant 18% increase from EOT to 1 year (116.4 mg/dL, P = 0.0058). Mean HDL did not change from baseline to EOT; however, from EOT to 1 year it increased significantly (36.4 to 41.7 mg/dL, 14.6%, P = 0.032) to a level not different from baseline ( P = 0.1). In contrast, among those treated with DAA-only therapy (28 patients) LDL increased significantly from baseline to 8 weeks post-EOT (85.9 to 102.1 mg/dL, 19%, P = 0.018), decreasing by 1 year (92.7 mg/dL, P = 0.076) to a level not significantly different from baseline ( P = 0.34). Pre and post treatment lipids differed between patients treated with IFN and those treated without. These findings suggest that direct interruption of viral replication with DAA therapy is associated with an increase in LDL and the decrease in LDL with IFN-based therapy is IFN-related. In both scenarios, treatment- associated changes do not appear to be sustained long term.